Effects of video tapes instruction on students achievement in english language (2005)
The study investigated the effect of video tape instruction on Senior Secondary School Students’ achievement in English Language. The study also examined the interaction effects of treatment and academic ability on students’ achievement in English Language. Simple random sampling was applied in selecting 213 students from four co-educational public secondary schools in Ibadan city. The study used a 2x2 factorial analysis of ANOVA and three null hypotheses were tested. Two instruments, namely English Language Achievement Test (ELAT) and Video Tape Guide for English Language (VTIGEL) which were the instructional strategies, were adopted from Ibode (2004). Data Analysis was done by using the Analysts of variance procedure. The results that there is significant main effect of treatment (video tape and control) on students’ achievement in English Language (FCi, 213 = 47.922., P>0.05). The result also revealed that there is significant main effect of academic ability on students’ achievement in English Language (FCi, 213) = 38.708P<0.5. The high academic ability students were significantly better than the low ability students in their achievement in English Language. The findings further revealed that there is no significant interaction' effect of treatment and students academic ability in their achievement in English Language (FCi, 213) P>005). Based on the findings of the study, recommendations were made for the gradual introduction of video tape instruction into the secondary school system as a supplement to the existing methods of instruction.